Europe's Hope for Recovery - McCloy, John J. (World Bank, Washington, DC, 2019)
John. J. McCloy, President of the International Bank for Reconstruction and Development, discussed the U.S. announcement of the European Recovery Program (Marshall Plan). This ambitious plan must be economically successful. The inherent strengths of Europe give reasonable assurance of the success of the Marshall Plan reorganization that is proposed. The problems of the continent do not appear insoluble. Human and materials assets, a sensible plan, good management, and sufficient new money are each elements that are fundamental to ensure success. External assistance should be conditioned upon economic reforms. Trade with Eastern Europe should be encouraged. Financing on this scale should be afforded primarily as grants rather than loans.